Evaluation of Physical Characteristics, Carbohydrate Content, and Sensory Preference of Suwar-suwir Caisim - Tejasari, Tejasari; Safitri, Lailya (Department of Technology of Agricultural product (THP) Jambi University, 2023)
Suwar-suwir is Jember-Indonesia’s traditional snack made from cassava fermented (tape) and sugar which give rises to very sweet flavor and sticky texture, causing consumer disfavor. This study aimed to determine the amount of mustard caisim powder added for fixing suwar-suwir texture, color and its sensory preference. This complete randomized controlled design tested effects of 6 level mustard caisim powder addition (Control=K=0, SF1=17, SF2=25, SF3=33, SF4=42, SF5=50%) toward suwar-suwir quality and sensory preference. The result showed that the addition significantly (P<0.05) affected physical properties and carbohydrate level (Fc>Ftab), and sensory liking preference (X2c >X2tab). The higher the addition of mustard caisim powder, the lower the texture value, the lower the color, the higher carbohydrate content. Suwar-suwir produced with 17% mustard caisim powder (SF1) has the best color, flavor, and overall performance. This suwar-suwir SF1 having more crunchy dense (163.2±4.80 mm/g.s,) more light green (29.59±0.29), high carbohydrate level (81.59±0.96%), high dietary fiber-TDF (20.8±0.01%), water soluble dietary fiber- SDF (6.29±0.002%) that lower than water insoluble dietary fiber - IDF (14.2± 0.01%). Based on the result analysis, it is recommend that the level addition of mustard caisim powder for improving suwar-suwir quality and image is 17 % from wet blend dough weight which produced suwar-suwir caisim SF1.